Pendidikan Karakter Melalui Aktivitas Zikir - Syafrudin Syafrudin (Universitas Indraprasta PGRI Jakarta, 2017)
The purpose of this research is to analyze (1) the teaching principles of dhikr in Al-Idrsisiyyah reciting group in Jakarta (2) the views of Al-Idrisiyyah reciting group members on character education (3) the effect of dhikr on character education. This research uses a qualitative method which is a descriptive research conducted in Al-Idrisiyyah reciting group Jakarta. This study uses primary data collection techniques from interviews, observations, informants, documentation and triangulation. While the secondary data are obtained from the profile of Al-Idrisiyyah Qur’an reciting group, the library, internet media, thesis, and other references. The research results indicate that dhikr activity will shape a better personality character. The more intensity of the dhikr performed by using a right method according to Qur’an and Sunnah, as well as guided by a murshid, the more benefits the dhikr activity will bring. The benefits are healthier physicality and spirits, more intelligent mind and peaceful soul.